New drag reduction design for tractor-trailers using CFD. (6th January 2011) - Hsu, Fu-Hung; Davis, Roger L.
Tractor-trailers have a higher drag coefficient than other vehicles due to their bluff-body shape. Over the years, numerous add-on devices have been invented to help reduce the drag. The current research investigates new add-on devices in the form of humps to reduce the base-drag of tractor-trailers. In the current investigation, computational fluid dynamics (CFD) in the form of unsteady Reynolds-averaged Navier-Stokes simulations is used to determine viable design strategies and optimise the new add-on device designs. A baseline model was built using an Ahmed body in both 2D and 3D. The predicted drag coefficient of the 3D Ahmed baseline model showed good agreement with experimental data. The 2D and 3D simulations with hump(s) showed some difference in drag reduction that was dependent on the hump geometry. A significant 3D effect existed. Results from the baseline validations as well as from simulations of tractor-trailer-like configurations with hump add-on devices are shown to demonstrate the drag reduction possible. While the hump is a conceptual design and may not be applied to full-size semi-truck trailers due to the height limit, it still offers a significant result which makes the applications on other smaller vehicles possible.